Study of Factors Influencing of Traditional Medicines In Community Hae-Coni, Post Administrative Baguia, Baucau Municipality 2025 - Moreira, Favião M.; Gusmão, Cipriana; Henrique, Surly E.F.R; Guterres, Rosita S.; Ximenes, Domingas de F. (Oshada, 2025)
Introduction: Timor-Leste has a culture and traditional knowledge regarding the use of medicinal plants for treating illnesses. Although the government provides free treating with a modern medicines, but mostly the community still uses traditional medicine’s for the treating. As a community Hae-Coni village, the people still continue to rely on traditional medicine due to limited access to modern healthcare. Which is a cultural factors to influence the traditional medicines healthcare. This analisysaim to continue information and determine the interaction between inherited and scientific knowledge to all community in Baguai Village. Objective: This research aim to identify the factors of influence the use of traditional medicines in the Hae-Coni community, Baguia Administrative Post. Methodology: The study employed a quantitative, descriptive- cross sectional design, using interviews and structured questionnaires applied to residents of the Hae-Coni community. Results: Further results: Cultural aspects: intergenerational transmission (15.1% use; 84.9% do not); spiritual and symbolic values (23.2% use; 76.8% do not). Access aspects: availability of medicinal plants (23.5% use; 76.5% do not); time to access traditional remedies (15.4% use; 84.6% do not). Experience aspects: effective practice (18% use; 82% do not); sources of information (20.5% use; 79.5% do not). Economic aspects: average income (18.2% use; 81.8% do not); lower income (20.2% use; 79.8% do not). Conclusion: based on Data analysis: Culture and access to healthcare services have a significant relationship with the use of traditional treatments, means In the Timor-Leste community regarding with the particularly in Baguia Administrative Post, social and cultural factors is a fundamental role in the preference for traditional medicines. The use of medicinal plants as an still alternative therapy on historically rooted, predating formal modern health services. It is because of the Limited access to modern healthcare, education of traditional medicine still lacking to change community health practices